IMPLIKASI PERGESERAN KONSEP GENDER TERHADAP FORMULASI HUKUM ISLAM - Kholida, Siti (Sekolah Tinggi Ilmu Syariah Abu Zairi Bondowoso, 2023)
This research is quantitative in nature. The data required in this study were collected using the following techniques: interviews, questionnaires and literature studies. The data collected was then processed by editing and coding techniques and then transferred into data recapitulation. Furthermore, the data that has been processed is analyzed by quantitative methods using different test techniques with the chi kwadrad formula and relationship test techniques with the product moment test formula. These techniques were used as estimation tools to determine the differences in attitudes based on the gender of the respondents with the rigidity and flexibility of their responses to the shifting concept of gender. Then the results of the analysis are presented in a descriptive-qualitative manner so as to illustrate the rigidity and flexibility of Islamic legal formulations and their gender shift patterns. From this research, it is assumed that the findings will be obtained that the responses of lecturers and students, both men and women, to the shifting concept of gender do not show any significant differences. In this case, lecturers and students, both male and female, respond to the shifting concept of gender with relatively similar attitudes and views and agree that gender is a socio-cultural construction of the standard image in the division of labor between men and women and not as nature as sex.